Conventional wisdom on roosting behavior of Australian flying‐foxes—A critical review, and evaluation using new data. Issue 19 (9th September 2021) - Lunn, Tamika J.; Eby, Peggy; Brooks, Remy; McCallum, Hamish; Plowright, Raina K.; Kessler, Maureen K.; Peel, Alison J.
Abstract: Fruit bats (Family: Pteropodidae) are animals of great ecological and economic importance, yet their populations are threatened by ongoing habitat loss and human persecution. A lack of ecological knowledge for the vast majority of Pteropodid species presents additional challenges for their conservation and management. In Australia, populations of flying‐fox species (Genus: Pteropus ) are declining and management approaches are highly contentious. Australian flying‐fox roosts are exposed to management regimes involving habitat modification, through human–wildlife conflict management policies, or vegetation restoration programs. Details on the fine‐scale roosting ecology of flying‐foxes are not sufficiently known to provide evidence‐based guidance for these regimes, and the impact on flying‐foxes of these habitat modifications is poorly understood. We seek to identify and test commonly held understandings about the roosting ecology of Australian flying‐foxes to inform practical recommendations and guide and refine management practices at flying‐fox roosts. We identify 31 statements relevant to understanding of flying‐fox roosting structure and synthesize these in the context of existing literature. We then contribute a contemporary, fine‐scale dataset on within‐roost structure to further evaluate 11 of these statements. The new dataset encompasses 13‐monthly repeat measures from 2, 522 spatially referenced roost trees across eight sites in southeastern Queensland and northeastern New South Wales. We show evidence of sympatry and indirect competition between species, including spatial segregation of black and grey‐headed flying‐foxes within roosts and seasonal displacement of both species by little red flying‐foxes. We demonstrate roost‐specific annual trends in occupancy and abundance and provide updated demographic information including the spatial and temporal distributions of males and females within roosts. Insights from our systematic and quantitative study will be important to guide evidence‐based recommendations on restoration and management and will be crucial for the implementation of priority recovery actions for the preservation of these species in the future. Abstract : Pteropodid bats are in decline globally. A major challenge for these species is that policies for conservation (roost restoration) and conflict management (roost modification or destruction) are often in direct contrast. Additionally, systematically informed, baseline ecological knowledge is limited for the vast majority of these species, so the impact and effectiveness of efforts to contribute to either conservation or conflict goals are unknown. This study is a systematic and multifaceted investigation into the roosting ecology of Australian flying‐foxes that aims to identify and empirically evaluate commonly held but anecdotal understandings about the ecology of these species, to contextualize management prescriptions in the context of species ecology.